(untitled) (Scientific journal of the Fergana State University, 2026)
This article analyzes the role and importance of logical problems in developing mathematical thinking among primary school students. Logical problems are considered an effective tool for activating students’ cognitive activity, as well as for developing analytical, comparative, generalizing, and reasoning skills. The methodological foundations for fostering independent and creative thinking during the process of solving logical problems are also discussed.